Wonderful Insects (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
Among invertebrates, insects are distinguished by their diversity and abundance. When we think of bugs, we always think of invisible and harmful creatures. But this is a big mistake! You will see this if you carefully study their world. In this article, you will learn about these unique characteristics of beetles.